Zirconium and Strip Crowns in the Area of Temporary Incisors of the Upper Jaw - Ravshanova Nazira Akramovna (Scientific Trends, 2024)
In case of extensive defects in hard tissues, as well as after the treatment of pulp diseases, the coating of teeth with artificial crowns is shown. The APD recommends the use of three options for artificial crowns: made of stainless steel, zirconium and Strip crowns. The term "Strip crowns" comes from the name of the process of removing the cap from the tooth after photopolymerization of the composite material. Strip crowns for baby teeth are special orthopedic structures that allow you to restore damaged teeth in young children.